Collaborative Governance dan Social Capital : Peran Pemerintah dan Non-Pemerintah dalam Disaster Management di Daerah Istimewa Yogyakarta - Prawira Yudha Pratama; Nurmandi Achmad (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
The study in this research is related to collaboration between government and social organizations in disaster management and how social capital grows in the community after the Merapi eruption. This study takes the case of the Mount Merapi Eruption Disaster Management in the Special Region of Yogyakarta. Whereas the method used in this research is qualitative-descriptive collected through journals, books, and important documents related to the eruption management of Mount Merapi eruption. The findings in this study indicate that after the eruption in 2010 grew disaster-aware communities. That is, social resilience in disaster preparedness in the face of Merapi eruption can be done by forming a disaster response community that organizes young people to be involved in disaster response. The community was formed because of the principles of humanity and volunteering. Besides this community was formed because of social cohesion, trust, and solidarity. In addition, this community was formed because of an active group in creating a network or a mass base so as to have a positive impact on the actual information to the local community. empowerment and political action are also separated from the formation of this disaster response community such as support from the government and all relevant stakeholders in providing training and empowerment to local communities. this collaboration is needed so that disaster is more systematic and planned.